2017
DOI: 10.1039/c7cc00169j
|View full text |Cite
|
Sign up to set email alerts
|

Insights into the role of nanostructure in the sensing properties of carbon nanodots for improved sensitivity to reactive oxygen species in living cells

Abstract: The surface states of carbon nanodots (CDs) were engineered by controlling the chemical structure on the surface of the CDs, which play an important role in the chemiluminescence sensing properties of CDs towards peroxynitrite. Their application in monitoring exogenous and endogenous release of peroxynitrite in living cells is demonstrated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 53 publications
0
16
0
Order By: Relevance
“…As part of a program to develop chemical probes for imaging reactive sulphur, 29 , 37 oxygen, 30 , 38 , 39 and nitrogen species, our laboratory has previously reported that isatin reacts with ONOO – via an oxidative decarbonylation reaction to generate anthranilic acid. 40 19 F NMR probes, 5-fluoroisatin and 6-fluorisatin, have been developed for selective detection of ONOO – that utilize this newly discovered transformation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As part of a program to develop chemical probes for imaging reactive sulphur, 29 , 37 oxygen, 30 , 38 , 39 and nitrogen species, our laboratory has previously reported that isatin reacts with ONOO – via an oxidative decarbonylation reaction to generate anthranilic acid. 40 19 F NMR probes, 5-fluoroisatin and 6-fluorisatin, have been developed for selective detection of ONOO – that utilize this newly discovered transformation.…”
Section: Resultsmentioning
confidence: 99%
“… 27 Nanoparticle-based methods have recently been reported for chemiluminescent ONOO – detection. 28 , 29 These probes rely on an interesting radical-pair mechanism to generate signal from the ONOO – decomposition products HO˙ and O 2 ˙ – . Although these systems do display good sensitivity, complementary approaches that operate via direct reaction with ONOO – are desirable.…”
Section: Introductionmentioning
confidence: 99%
“…Confinement effects introduced into the CL field amplified CL emission from CDs. Furthermore, surface oxygenous functional groups in the CDs played an important role in CL intensity . Due to the correlation between CL intensity in the CDs−ONOO − mixed system and the content of C−O group‐related O states in CDs, a novel platform for screening O states in CDs was developed using a rapid, effective CL nanoprobe .…”
Section: Carbon Nanodotsmentioning
confidence: 99%
“…The CL response intensity for ONOO − was enhanced as the C–O group content in CDs increased. Based on this property, an ultrasensitive CL nanoprobe for ONOO − was designed and used to monitor endogenous and exogenous ONOO − in living cells . The influence of surface functional groups on CL performance of CDs has been shown by other research groups .…”
Section: Carbon Nanodotsmentioning
confidence: 99%
“…Since then, they have become an object of great research interest in the materials science community [6][7][8]. In fact, compared to conventional inorganic semiconductor-based quantum dots, they exhibit peculiar features, like high photostability, nontoxicity, water solubility, and lowcost [9][10][11][12][13][14][15][16][17][18]; see Figure 1. Their synthesis methods are cheap and sustainable [20] and usually are divided into two main categories: top-down and bottom-up methods [21].…”
Section: Introductionmentioning
confidence: 99%